Words into worlds : learning a second language through process drama - Kao, Shin-Mei (Ablex, 1998)
An analysis of learning a second language through process drama. Topics covered include: evoking dramatic moments in second language learning and teaching; the nature of teacher-student interaction in drama-orientated language classrooms; and the psycho-social aspect of drama on learning